Análise de risco do aproveitamento da água de chuva para uso não potável em edificações - Bassanesi, Karine (2014)
This master degree contains a literature review on the conservation of water, rainwater utilization, quality and water treatment, legislation and risk analysis. Was verified that rainwater utilization systems vary widely in type and would be important to be able to correlate the precipitated water, uses and models for each situation. And for this work was used the risk analysis focusing the preliminary hazard analysis. A bibliographic review carried out presented some guides and legislation that could complete quality control parameters for non-potable rainwater utilization, and determine the time to review these parameters to control the operation of the system. The study's preliminary analysis was used to study the greatest dangers in the use of rain-related water quality system, critical control points, the user risks, control measures and mitigation measures. For the case study was addressed the same preliminary hazard analysis for knowledge about the contamination of rainwater in relation to the control parameters and on their own knowledge of project development for rainwater utilization. Through the two analyzes a proposal of guidelines was performed for implantation of rainwater utilization system for the case study and there is a possibility of a real fitness for safe use.